Expressed sequence tags in venomous tissue of Scorpaena plumieri (Scorpaeniformes: Scorpaenidae) - Fábio L. S. Costa; Maria E. De Lima; Adriano C. Pimenta; Suely G. Figueiredo; Evanguedes Kalapothakis; Carlos E. Salas (Neotropical Ichthyology)
Species of the family Scorpaenidae are responsible for accidents and sporadic casualties by the shore they inhabit. The species Scorpaena plumierifrom this family populate the Northeastern and Eastern coast of Brazil causing human envenomation characterized by local and systemic symptoms. In experimental animals the venom induces cardiotoxic, hypotensive, and airway respiratory effects. As first step to identify the venom components we isolated gland mRNA to produce a cDNA library from the fish gland. This report describes the partial sequencing of 356 gland transcripts from S. plumieri. BLAST analysis of transcripts showed that 30% were unknown sequences, 17% hypothetical proteins, 17% related to metabolic enzymes, 14% belonged to signal transducing functions and the remaining groups (7-8%) composed by gene related with expressing proteins, regulatory proteins and structural proteins. A considerable number of these EST were not found in available databases suggesting the existence of new proteins and/or functions yet to be discovered. By screening the library with antibodies against a lectin fraction from S. plumierivenom we identified several clones whose DNA sequence showed similarities with lectins found in fish. In silicoanalysis of these clones confirm the identity of these molecules in the venom gland of S. plumieri.